(untitled) - Yousaf Kamran; Humaira Imran; Aqsa Saleem; Abdul Basit Khan; Seerat Mustafa; Dr. Nijat Ullah Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The primary objective of this study was to investigate the applicability of Systemic Functional Grammar, a linguistic novelty pioneered by renowned linguist M.A.K. Halliday. The theory lays out a perspective on how linguistic processes function in literary works. The purpose of this research is to identify the essential components of Ahmed Ali’s Twilight in Delhi. The novel was examined using ideational, interpersonal, and textual analysis, three of the theory’s primary functional methodologies. The study examined active and passive voice sentences and transitivity patterns. Additionally, it looked at the relationships between the individuals participating in the process. The textual meaning and sense that resulted from all of the aforementioned discoveries were then explored. The textual meaning and sense that resulted from all of the previous findings were then explored. In the finale, it looked again for the themes and message of the novel.